The Influence of Educational Communication Media on Civic Literacy of Students at Madrasah Ibtidaiyah Ismaria Al-Quraniyyah - Muhammad Wahyu Dhiva; Budhi Waskito; Wawan Hernawan (Universitas Dharmawangsa Medan, 2026)
further indicated that Grade VI students experienced more diverse and intensive media utilization, which corresponded with higher civic literacy levels. The study concludes that the integration of This study was motivated by the uneven level of civic literacy among students at Madrasah Ibtidaiyah Ismaria Al-Quraniyyah, as reflected in the gap between expected learning outcomes and actual achievement in Civic Education. The research aimed to examine the use of educational communication media in Civic Education learning and to analyze the effects of visual learning media, interactive educational media, and simple digital media on students’ civic literacy. A mixed-method approach with a convergent design was employed, integrating qualitative data from interviews and documentation with quantitative data collected through questionnaires administered to 68 Grade I and Grade VI students. The findings revealed that visual media, interactive educational media, and simple digital media each had a positive and significant effect on civic literacy. Simple digital media demonstrated the strongest influence among the three variables. Simultaneous analysis showed that these media collectively explained 80.5% of the variance in students’ civic literacy. Qualitative findings visual, interactive, and digital educational media effectively enhances civic literacy and highlights the importance of strengthening digital infrastructure and teachers’ digital competencies to improve citizenship education at the elementary level.